Effect of Xylocaine spray for analgesia during amniocentesis: a randomized controlled trial - Panupun Homkrun (2020)
© 2019 John Wiley & Sons, Ltd. Objective: To compare the effect of Xylocaine spray on pain score during amniocentesis. Methods: Singleton pregnant women undergoing amniocentesis were recruited. Each participant was randomly assigned into three groups. Group 1 (Xylocaine spray): 1 min before the procedure, 8 puffs (80 mg) of 10% Lidocaine spray were sprayed on abdominal wall: group 2 (placebo): 8 puffs of sterile normal saline were sprayed: and group 3 (control): no spray was used. The participants rated their pain through a 10-cm visual analog scale before, during, and 30 min after amniocentesis. Main outcome of study was difference in pain score among three groups. Results: A total 570 pregnant women participated; 191 in the Xylocaine group, 193 in placebo group, and 186 in control group. Baseline pain was not different. The median procedural pain score was significantly different (2.3, 3.3, and 2.8 respectively; p 0.001). Post-hoc analysis showed that the procedural pain score in Xylocaine group was significantly lower than placebo or control group (p value <0.001 and 0.02, respectively). However, the pain score 30 min after procedure was not different. Conclusion: Xylocaine spray can significantly decrease pain during amniocentesis, however, the clinical significance is unclear given that the procedure-related discomfort is mild and short-lived.